2009
DOI: 10.1038/jes.2009.21
|View full text |Cite
|
Sign up to set email alerts
|

Occupational exposure to diesel engine exhaust: A literature review

Abstract: Diesel exhaust (DE) is classified as a probable human carcinogen. Aims were to describe the major occupational uses of diesel engines and give an overview of personal DE exposure levels and determinants of exposure as reported in the published literature. Measurements representative of personal DE exposure were abstracted from the literature for the following agents: elemental carbon (EC), particulate matter (PM), carbon monoxide (CO), nitrogen oxide (NO), and nitrogen dioxide (NO 2 ). Information on determina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
153
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 193 publications
(159 citation statements)
references
References 57 publications
5
153
1
Order By: Relevance
“…Occupational studies showed that there may be a greater incidence of cough, phlegm, and chronic bronchitis among those exposed to diesel CE than among those not exposed (Pronk et al, 2009). Reductions in pulmonary function have also been reported following occupational exposures in chronic studies (Rudell et al, 1996).…”
Section: Hhs Public Accessmentioning
confidence: 88%
See 2 more Smart Citations
“…Occupational studies showed that there may be a greater incidence of cough, phlegm, and chronic bronchitis among those exposed to diesel CE than among those not exposed (Pronk et al, 2009). Reductions in pulmonary function have also been reported following occupational exposures in chronic studies (Rudell et al, 1996).…”
Section: Hhs Public Accessmentioning
confidence: 88%
“…This was because of the following two reasons: (1) Several studies reported increased acute respiratory symptoms, chronic bronchitis, and aggravation of asthma upon exposure to PM (Pronk et al, 2009;Rudell et al, 1996), and (2) of the six mouse strains tested, BALB/cJ mice were reported to be the best inbred strain that closely mimics the phenotype of human occupational asthma (De Vooght et al, 2010).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent review by Pronk et al [5] reported literature on occupational uses of diesel engines and subsequent personal exposure to diesel exhausts. Over 10,000 assessments of elemental carbon, particulate matter, carbon monoxide and nitric oxides measurements were included; with 32% on road exposures; 68% off road exposures (including 30% mining and 15% rail).…”
Section: Exposure To Diesel Exhaustmentioning
confidence: 99%
“…Hazardous levels of diesel exhaust can be found in occupations ranging from mining to driving diesel-fuelled trucks or forklifts [5]. Durability and fuel efficiency have lead to an increase in the use of diesel engines.…”
Section: Introductionmentioning
confidence: 99%